Earning excitement - Nourigat, Paul.; Nourigat, Natalie ([Portland, Or.] : FarBeyond Pub., 2010)
Chelsea and her brother Jack learn how to earn enough money to buy the Red Flyer radio-controlled race car they want. Includes tips for kids and parents and a financial glossary.
5.3
3-6
Keywords: Money-making projects for children -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Money-making projects -- Fiction; Brothers and sisters -- Fiction; Money-making projects for children -- Fiction; Siblings -- Fiction; Money -- Fiction; Finance, Personal -- Fiction; Saving and investment -- Fiction; Moneymaking projects -- Fiction; Business enterprises -- Fiction